Pengaruh Blended Learning di Masa Pandemi terhadap Hasil Belajar Siswa Mata Pelajaran PAI Kelas V di SDN 1 Margalaksana Kab. Bandung Barat - Anisa Indah Sabila; Ayi Sobarna (Bandung Conference Series: Islamic Education, 2022)
Abstract. Due to the COVID-19 pandemic, schools implemented distance learning to stop the spread of the corona virus in the school environment. So this study was used to examine more deeply the effect of blended learning on student learning outcomes in the thesis entitled ‘The Effect of Blended Learning in the Pandemic Period on the Learning Outcomes of Class V PAI Subjects at SDN 1 Margalaksana Kab. West Bandung’. This study aims to (1) determine the implementation of blended learning in PAI class V subjects at SDN 1 Margalaksana during the pandemic. (2) Knowing the learning outcomes of the fifth grade PAI subjects at SDN 1 Margalaksana. (3) Analyzing the effect of the implementation of blended learning during the pandemic of PAI subjects on the learning outcomes of class V students at SDN 1 Margalaksana (4) Knowing the supporting and inhibiting factors faced in the implementation of blended learning of PAI subjects for class V at SDN 1 Margalaksana. This study uses a quantitative approach. This study was used to examine the effect of blended learning on the learning outcomes of fifth grade students at SDN 1 Margalaksana by taking the results of the student report cards after being given treatment. This research method uses the correlation method which aims to determine how much influence blended learning has on the learning outcomes of fifth grade students. The results of this study use analysis on the t-test on each dependent variable, namely (1.737>1721) on the Y1 variable, namely the affective learning outcomes of aspects of spiritual attitudes, (1.767>1.721) on Y2, namely the affective learning outcomes of social attitudes, (1,069<1.721) in Y3 is cognitive learning outcomes and (1.739>1.721) on Y4 psychomotor learning outcomes. Thus, this shows that Ha is accepted and H0 is rejected, which means that there is an effect of blended learning during the pandemic on the learning outcomes of fifth graders at SDN 1 Margalaksana. Abstrak. Akibat adanya pandemi covid-19 sekolah menerapkan pembelajaran jarak jauh untuk memutus persebaran virus corona di lingkungan sekolah. Maka penelitian ini digunakan untuk meneliti lebih dalam mengenai pengaruh blended learning terhadap hasil belajar siswa dalam skripsi yang berjudul ‘Pengaruh Blended learning di Masa Pandemi Terhadap Hasil Belajar Siswa Mata Pelajaran PAI Kelas V di SDN 1 Margalaksana Kab. Bandung Barat’. Penelitian ini bertujuan untuk (1) Mengetahui pelaksanaan blended learning pada mata pelajaran PAI kelas V di SDN 1 Margalaksana di masa pandemic. (2) Mengetahui hasil belajar mata pelajaran PAI siswa kelas V di SDN 1 Margalaksana. (3) Menganalisis pengaruh diterapkannya blended learning di masa pandemi mata pelajaran PAI terhadap hasil belajar siswa kelas V di SDN 1 Margalaksana (4) Mengetahui faktor pendukung dan penghambat yang dihadapi pada pelaksanaan blended learning mata pelajaran PAI kelas V di SDN 1 Margalaksana. Penelitian ini menggunakan pendekatan kuantitatif. Penelitian ini digunakan untuk menguji pengaruh blended learning terhadap hasil belajar siswa kelas V SDN 1 Margalaksana dengan mengambil hasil rapot siswa setelah diberikan perlakuan (treatment). Metode penelitian ini menggunakan metode korelasional yang bertujuan untuk mengetahui seberapa besar pengaruh blended learning terhadap hasil belajar siswa kelas V. Hasil penelitian ini menggunakan analisis pada uji t pada setiap variebel terikat yaitu (1.737>1721) pada variabel Y1 yaitu hasil belajar afektif aspek sikap spiritual, (1.767>1.721) pada Y2 yaitu hasil belajar afektif aspek sikap sosial, (1.069<1.721) pada Y3 yaitu hasil belajar kognitif dan (1.739>1.721) pada Y4 hasil belajar psikomotorik. Dengan demikian hal ini menunjukkan bahwa Ha diterima dan H0 ditolak yang artinya terdapat pengaruh blended learning di masa pandemi terhadap hasil belajar siswa kelas V SDN 1 Margalaksana.